Meta-Analysis: Are Acupressure and Birthing Ball Exercise Associated with Labor Pain? - Astuti, Susiana Yuni; Budihastuti, Uki Retno; Prasetya, Hanung (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Management of pain in labor is identified as one of the most important topics related to pregnancy and childbirth. Acupressure and birthing ball exercise are one of the non-pharmacological methods of managing labor pain to help mothers cope with the labor process. This management can relieve pain sensations by increasing the woman's well-being, comfort, and sense of control in labor. This study aims to estimate the effect of acupressure and birthing ball exercise on labor pain. Subjects and Method: This was a systematic review and meta-analysis conducted using PRISMA flow diagrams. Search articles through journal databases including: PubMed, Science Direct, Google Schoolar and SpingerLink by selecting articles published in 2010-2021. The keywords used are (“labor pain” OR labor pain) “AND (“acupressure” OR “acupressure hegu”) AND (“birthing ball” OR “birthing ball exercise”) AND “randomized controlled trial”. Inclusion criteria were full paper articles with Randomized Controlled Trial (RCT) research methods, the size of the relationship used with Mean SD, the intervention given was acupressure and birthing ball exercise, research subjects were mothers in the first stage of active labor. Eligible articles were analyzed using the Revman 5.3 application. Results: Meta-analysis of 16 articles showed results for acupressure (SMD -1.29; 95% CI= -2.35 to 0.24; p=0.02) and birthing ball exercise (SMD -0.73; 95% CI= -1.56 to 0.11; p=0.09). Conclusion: Acupressure and birthing ball exercise each have an effect on reducing labor pain.